2023
DOI: 10.3389/fmicb.2023.1128956
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolites of Dendrobium nobile were positively correlated with representative endophytic fungi at altitude

Abstract: IntroductionAltitude, as a comprehensive ecological factor, regulates the growth and development of plants and microbial distribution. Dendrobium nobile (D. nobile) planted in habitats at different elevations in Chishui city, also shows metabolic differences and endophytes diversity. What is the triangular relationship between altitude, endophytes, and metabolites?MethodsIn this study, the diversity and species of endophytic fungi were tested by ITS sequencing and metabolic differences in plants were tested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In our study, it was found that the content of these two substances showed an increasing trend with increasing altitude. A similar result was also observed in other plants, such as Dendrobium nobile [42]. This finding is consistent with previous research conducted on tea plants under simulated high-altitude conditions, wherein aroma compound contents increased due to upregulated expressions of key structural genes [9].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was found that the content of these two substances showed an increasing trend with increasing altitude. A similar result was also observed in other plants, such as Dendrobium nobile [42]. This finding is consistent with previous research conducted on tea plants under simulated high-altitude conditions, wherein aroma compound contents increased due to upregulated expressions of key structural genes [9].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Hyphodiscus is associated with the production of specific fatty acids that are associated with growth promotion in Dendobium nobile (Zhao et al, 2023). A number of the non-Sordariomycete fungi identified in this study also have potential beneficial attributes.…”
Section: Identified Onf Are Known Endophytes With Potential Beneficia...mentioning
confidence: 65%
“…Fusarium extracts have also been shown to be important in orchid growth and development, enhancing in vitro growth of Dendrobium moniliforme (Shah et al., 2019) and stimulating germination (Li et al., 2021). Similarly, Hyphodiscus is associated with the production of specific fatty acids that are associated with growth promotion in Dendobium nobile (Zhao et al., 2023). A number of the non‐Sordariomycete fungi identified in this study also have potential beneficial attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that the community and abundance of endophytes in 1-year-old D. nobile were significantly different from those in older plants. It has also been reported that some endophytic fungi can positively promote the accumulation of fatty acid metabolites in D. nobile by infestation and colonization ( Zhao et al, 2023 ). Therefore, we hypothesize that endophyte colonization in 1-year-old D. nobile is closely related to the high content of dendrobine alkaloids.…”
Section: Introductionmentioning
confidence: 98%